Eksistensi Reforma Agraria Dalam Penyelesaian Sengketa Agraria - Khoirotul Hijriah, Nurul (Recital Review, 2024)
The purpose of this paper is to identify and analyze the existence of agrarian reform in the current resolution of agrarian disputes. The existence of agrarian reform in the settlement of agrarian disputes has not fulfilled the expected goals. The continued increase in the number of agrarian dispute cases reflects that the existence of agrarian reform needs to be used as the basis for (national) economic development in Indonesia. In addition, it is very necessary to improve and evaluate the policies drafted after the UUPA, so that the objectives of agrarian reform can proceed as they should and can have a welfare impact on all levels of society.